IMPLEMENTASI ICE BREAKING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN PJOK DI SMK NEGERI 11 MALANG - Alifta Rahma Hidayah; Eko Hariyanto; Dwi Novianto (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA (UTP), 2026)
This study investigates the effectiveness of ice breaking activities in enhancing student learning motivation in Physical Education, Sports and Health (PJOK) lessons through a Classroom Action Research (PTK) approach. The research was carried out in two cycles, each comprising planning, implementation, observation, and reflection stages. The subjects were 34 students of class X TKR 3 at SMK Negeri 11 Malang. Results showed a meaningful improvement in student motivation, from an average of 52.64% in Cycle I to 73.81% in Cycle II—a gain of 21.17%. This improvement indicates that the integration of ice breaking techniques creates a more enjoyable and participatory learning environment, which in turn stimulates students' intrinsic motivation. The findings support the importance of adopting innovative, student-centered instructional strategies in PJOK to achieve optimal learning outcomes. This research contributes evidence that brief, playful warm-up activities can shift classroom dynamics from passive to active engagement, particularly in physical education settings where enthusiasm and physical readiness are crucial for effective learning.